Value-added manufacturing, growth and inflation: dynamic panel threshold perspective - Aktaş, Emin Efecan; Erdem, Lokman Salih (Technological and Economic Development of Economy, 2026)
This study pioneers the exploration of inflation’s nonlinear role in the nexus between value-added manufacturing and economic growth, employing a dynamic panel threshold model for 38 Organisation for Economic Co-Operation and Development (OECD) countries from 1980 to 2023. Unlike prior research, it uniquely identifies an inflation threshold (4.4954%) that alters the manufacturing-growth relationship. Below this threshold, value-added manufacturing significantly boosts economic growth, while above it, growth declines despite manufacturing process, revealing a novel nonlinear dynamic. Utilizing advanced methodologies like System Generalized Method of Momemnts (GMM) and Diallo’s (2020) dynamic panel threshold approach, the study addresses endogeneity and cross-sectional dependence, offering robust insights. These findings highlight inflation’s critical influence on manufacturing’s growth effects, urging policymakers to prioritize price stability to maximize manufacturing’s economic contributions. This research enriches the literature by integrating inflation thresholds into growth models, providing fresh policy implications for sustainable economic strategies in OECD economies.First published online 28 January 2026